2013
DOI: 10.1039/c3ra23307c
|View full text |Cite
|
Sign up to set email alerts
|

Polydopamine-coated graphene as multifunctional nanofillers in polyurethane

Abstract: Polyurethane nanocomposites incorporated with polydopamine (PDA)-coated graphene sheets (D-Graphene) were fabricated by solution blending. It is found that the interfacial PDA layers not only facilitate the dispersion of the graphene sheets in the polymer matrix, but also strengthen the stress transfer from the polymer matrix to the filler, enhancing tensile and thermo-mechanical properties of the nanocomposites and decreasing the electrical conductivity percolation threshold of the nanocomposites. Furthermore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
72
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(73 citation statements)
references
References 39 publications
1
72
0
Order By: Relevance
“…To assess the overall performance of these composites, the electrical and mechanical properties of these graphene based composites are compared with the results in literature as shown in Table 3 [20,32,36,[56][57][58][59]. It is demonstrated that among these surface modified graphene reinforced TPU composites, current study exhibits relative high conductivity with the same amount of filler content (1 wt.%).…”
Section: Electrical Property Of Nanocompositesmentioning
confidence: 81%
See 1 more Smart Citation
“…To assess the overall performance of these composites, the electrical and mechanical properties of these graphene based composites are compared with the results in literature as shown in Table 3 [20,32,36,[56][57][58][59]. It is demonstrated that among these surface modified graphene reinforced TPU composites, current study exhibits relative high conductivity with the same amount of filler content (1 wt.%).…”
Section: Electrical Property Of Nanocompositesmentioning
confidence: 81%
“…Comparing with neat TPU, TPU/GO demonstrates almost the same level of stress in the low modulus region; where TPU/GO/PVP demonstrate slightly higher stress in that particular region; meanwhile, TPU/ RGO/PVP demonstrates the highest stress among these composites. These filler are most likely dispersed around the soft segments of TPU [36], the stress observed in the low modulus region is thought to be largely related with the filler dispersion as well as interfacial interaction between filler and TPU matrix. Comparing TPU/GO/PVP with TPU/GO, PVP coating could enhance interfacial interaction between GO and TPU, therefore, higher stress is observed.…”
Section: Mechanical Propertiesmentioning
confidence: 97%
“…In another case, Yang et al modified graphene sheets with polydopamine (PDA) [81]. The as-obtained PDA-coated graphene sheets (D-Graphene) was then used to blend with PU by solution blending.…”
Section: Concentration Dispersion and Conductivity Of Graphenementioning
confidence: 98%
“…Tunneling is the dominant mechanism for PGNs whose I-V curves can be characterized by power law, while the linear I-V relationship following Ohm's law means the dominant mechanism of direct contact [18]. For example, the conductivity of forementioned PU/D-Graphene was supposed to be tunneling dominant [81]. Yang et al [14] established that there is a close relationship between the EMI SE of conductive polymer-based composites and its electrical conductivity.…”
Section: Electrical Conductivity Of Polymer Matrixmentioning
confidence: 98%
“…In general, shielding performance can be raised effectively by plate-like particles [5], while conductivity and mechanical strength can be upgraded efficiently by particles with high aspect ratios [6][7][8]. As one of methods for controlling particle shape, the hydrothermal crystallization using capping agent has also been proposed [9].…”
Section: Introductionmentioning
confidence: 99%